Establishment of a bioluminescence-based bioassay for the detection of dioxin-like compounds. (May 2013) - Wang, Bo-Jeng; Liao, Yung-Feng; Tung, Ying-Tsen; Yih, Ling-Huei; Hu, Cho-Chun; Lee, Hsinyu
Abstract Dioxin and dioxin-like compounds are among the most prevalent and toxic environmental pollutants. At present, analytical chemical techniques are considered the gold standard for detection of dioxins. Here, we describe a highly sensitive and cost-effective alternative, based on bioluminescence and bioluminescence resonance energy transfer (BRET). Upon binding to dioxin, aryl hydrocarbon receptor (AHR) dissociates from HSP90 and subsequently translocates to the nucleus, where it interacts with AHR nuclear translocator (ARNT). We generated cell lines that stably co-express a fusion protein of AHR and Renilla luciferase (AHR–RL) and either HSP90 or ARNT tagged with yellow fluorescent protein (HSP90-YFP or ARNT-YFP). The fluorescent signals of YFP are activated by the emission of RL while the interactions between AHR and HSP90 (or ARNT) were monitored. Application of 3-methylcholanthrene, the AHR agonist, enhances BRET signals in cells co-expressing AHR–RL, AIP-His, P23-His and ARNT-YFP (AAPA cells), while suppressing BRET signals in cells co-expressing AHR–RL, AIP-His, P23-His and HSP90-YFP (AAPH cells). In addition, dioxin treatment reduced Renilla luminescence in AAPH cells in a concentration-dependent manner, due to the degradation of AHR. Intriguingly, the detection limit for dioxin in our AHR degradation assay was as low as 10–17 M. This work highlights the potential of AHR–RL degradation assays to detect dioxin-like pollutants.